Social representations about the formative process of Brazil's rural areas' teachers and EJA (Young Adults and Adults' Education): the reality of the Paraense Amazon - Alessandra Sampaio Cunha; Armando Paulo Ferreira Loureiro; Joana d'Arc de Vasconcelos Neves (Universidade Federal do Norte do Tocantins, 2021)
This article articulates the debate on the initial training of rural teachers, Youth and Adult Education (EJA) and the psychosocial processes that guide the training of teachers to / in rural schools. To this end, it embarks on the theoretical field of Social Representations (RS) in order to analyze the senses and meanings of teachers who completed the Degree Course in Rural Education under the contribution of their training process to work in the EJA / countryside in the Amazon Paraense. This is a qualitative study of the exploratory / explanatory type that used the questionnaire and the semi-structured interview to collect the data. The results of this study indicate that the Social Representations of the teachers about the Degree in Rural Education are enrolled in meanings that reaffirm that specific training, geared to the needs of rural people, contributed with knowledge and teaching-learning processes that potentialized (re) thinking and innovating pedagogical practices. The rural teachers also see the course as a space for the production of differentiated knowledge of being and becoming a teacher of EJA in the field, insofar as they help to understand the social and political dynamics of the peasant way of life in the Brazilian Amazonian rural areas.